2004
DOI: 10.1245/aso.2004.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Cisplatin Polymer in Limb-Sparing Surgery for Canine Osteosarcoma

Abstract: Local tumor recurrence may be decreased after limb-sparing surgery by use of biodegradable implants impregnated with chemotherapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 34 publications
5
82
0
1
Order By: Relevance
“…309 However, unlike amputation, marginal resection of the primary tumor in limb sparing techniques can result in the rate of local recurrence to be as high as 28%. 310 Therefore, biodegradable bone scaffolds capable of sustained and controlled drug elution are ideal candidates for limb sparing treatments in osteosarcoma patients. One group recently investigated an open cell polylactic acid scaffold containing 8 wt % cisplatin (platinum-based chemotherapeutic) in an animal model.…”
Section: Antibiotics and Chemotherapeuticsmentioning
confidence: 99%
“…309 However, unlike amputation, marginal resection of the primary tumor in limb sparing techniques can result in the rate of local recurrence to be as high as 28%. 310 Therefore, biodegradable bone scaffolds capable of sustained and controlled drug elution are ideal candidates for limb sparing treatments in osteosarcoma patients. One group recently investigated an open cell polylactic acid scaffold containing 8 wt % cisplatin (platinum-based chemotherapeutic) in an animal model.…”
Section: Antibiotics and Chemotherapeuticsmentioning
confidence: 99%
“…Use of locally delivered chemotherapy has been explored extensively for dogs with naturally occurring canine tumors (2, 3, 6, 2325). Wound implantation of cisplatin-impregnated open-cell polylactic acid (OPLA-Pt) was shown to be tolerated and effective against metastasis and local recurrence in dogs receiving limb-sparing surgery (2, 6, 2325).…”
Section: Discussionmentioning
confidence: 99%
“…Wound implantation of cisplatin-impregnated open-cell polylactic acid (OPLA-Pt) was shown to be tolerated and effective against metastasis and local recurrence in dogs receiving limb-sparing surgery (2, 6, 2325). Following wound implantation of either 82 or 54 mg/m 2 OPLA-Pt, the combined mean area under the curve for total serum platinum concentration was almost 30 times greater than that after a single i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported nephrotoxicosis in up to 73% of dogs undergoing cisplatin therapy. 10 However, different protocols, dosing regimens, and definitions of nephrotoxicosis make it difficult to compare the frequency of this adverse effect. Similar to these results, approximately one third of people treated with cisplatin chemotherapy have irreversible renal damage.…”
Section: Discussionmentioning
confidence: 99%